2022
DOI: 10.3390/children9121855
|View full text |Cite
|
Sign up to set email alerts
|

Family Influences on the Dental Caries Status of Children with Special Health Care Needs: A Systematic Review

Abstract: Oral health is a likely source of health inequalities in children with special health care needs (CSHCN), according to multiple studies. This systematic review aimed to explore the evidence of family influence—as well as family features, such as societal variables and parents’ perspectives—on these children’s dental caries status. Embase, Ebsco, Scopus, PubMed, and Web of Science databases were all searched. All cross-sectional research published on the variables of family impact ranging from 2010 to 2021 were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 48 publications
1
1
0
Order By: Relevance
“…38,39 Most of the studies included that explored the familial impact observed that there was a strong impact of the child's or adolescent's oral health condition on the change in family routine, familial finances, sleep patterns, time off from work, emotional well-being and the stress or concerns parents felt on a regular basis. This was confirmed by recent studies, 40 which explored the family influences on the oral health of children with SHCNs.…”
Section: Discussionsupporting
confidence: 71%
“…38,39 Most of the studies included that explored the familial impact observed that there was a strong impact of the child's or adolescent's oral health condition on the change in family routine, familial finances, sleep patterns, time off from work, emotional well-being and the stress or concerns parents felt on a regular basis. This was confirmed by recent studies, 40 which explored the family influences on the oral health of children with SHCNs.…”
Section: Discussionsupporting
confidence: 71%
“…In addition, any improvements in orthodontic treatment protocols or biomaterials that might reduce bacterial adhesion or colonization should be noted for further evaluation and study. These data could be included in future prospective studies of this organism that will likely follow, which could be valuable information to include in future prospective studies of Slackia exigua [31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…Estas condições são consideradas de risco para o desenvolvimento de doenças bucais (Santos et al, 2013). Além disso esses pacientes apresentam dificuldades na escovação, diminuição do fluxo salivar, ingestão de medicamentos e dietas limitadas (Anwar et al, 2022).…”
Section: Revisão De Literaturaunclassified
“…A Organização Mundial da Saúde (OMS) definiu como deficiência, alterações que podem ser em relação à estrutura corporal ou ao funcionamento mental (Anwar et al, 2022). Pacientes com necessidades especiais são definidos por terem quaisquer deficiências físicas, de desenvolvimento, mentais, sensoriais, comportamentais, cognitivas ou emocionais que requeiram tratamento diferenciado, intervenção especial e/ou uso de serviços ou programas especializados.…”
Section: Introductionunclassified